(untitled) (Modern education and development, 2024)
This article examines the use of new pedagogical technologies in the Latin language course program. Existing methods of teaching Latin in medical universities are analyzed. The need for using innovative approaches to teaching, including computer training, training using interactive methods, distance learning through video conferences, and extracurricular training is identified and substantiated.